Allergic Reactions to Residual Monomers in Acrylic Denture Bases: A Systematic Review of Randomized Controlled Trials and Primary Studies - Junez Kanisa; Adethyan Wira Gama; Ayub Quisa (The Indonesian Journal of General Medicine, 2026)
Introduction: Residual monomers — principally methyl methacrylate (MMA) and 2-hydroxyethyl methacrylate (2-HEMA) — persist in conventional polymethyl methacrylate (PMMA) denture bases following incomplete polymerization and are associated with a spectrum of adverse biological reactions, including Type IV contact hypersensitivity, allergic contact stomatitis, burning mouth syndrome (BMS), and occupational allergic contact dermatitis in dental personnel. Methods: he study strictly adhered to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 guidelines. Two independent reviewers screened records using PRISMA 2020 methodology. Risk of bias was assessed with Cochrane RoB 2.0 and the Newcastle-Ottawa Scale. A minimum of 15 studies and 10 outcome domains were pre-specified. Results: Fifteen studies (n = 2,287 participants/specimens) met inclusion criteria. Autopolymerized resins harbored residual MMA of 2.2–7.5% w/w vs. 0.11–0.90% w/w for heat-cured PMMA and 0.02–0.12% w/w for CAD/CAM-milled PMMA. Patch-test positivity to MMA/2-HEMA among symptomatic denture wearers ranged from 4–27%. Ten pre-specified outcome domains were fully analyzed. GRADE certainty: HIGH for residual MMA quantification and cytotoxicity data; MODERATE for clinical sensitization prevalence and occupational exposure outcomes. Discussion: Evidence confirms a dose-dependent relationship between residual monomer elution and mucosal/immunological reactivity. Autopolymerized resins confer the greatest risk. Post-polymerization water immersion at 50°C for ≥60 minutes and use of CAD/CAM pre-polymerized PMMA substantially reduce allergenic burden. Conclusion: Residual monomers in acrylic denture bases constitute a clinically significant, preventable source of contact hypersensitivity. Clinicians should prioritize heat-cured or digitally fabricated PMMA, implement post-polymerization protocols, and employ standardized acrylate patch testing in symptomatic patients.